MULTIMODAL DISCOURSE IN MOBILE LANGUAGE LEARNING APPLICATIONS - Lucia Fernandez (International Journal of Literature and Language Studies, 2026)
This article investigates multimodal discourse in mobile language learning applications within the broader field of linguistics and applied language studies. The study uses lesson screens, feedback messages, icons, sounds, and visual prompts from three popular mobile language learning applications and applies multimodal discourse analysis focusing on image, colour, layout, sound, feedback, and learner positioning. The main finding is that apps used badges, progress bars, friendly characters, and immediate feedback to create motivation and guide learner behaviour. The article argues that language learning apps should be evaluated not only for linguistic content but also for the semiotic design of learning experience. The discussion is relevant to researchers, teachers, curriculum designers, and graduate students who need concise but systematic models of linguistic inquiry.